2021
DOI: 10.3390/jcm10040588
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Penetration of Low-Dose Atropine Eye Drops

Abstract: Major studies demonstrating the inhibition of myopia in children and juveniles by low-dose atropine eye drops provide little information on the manufacturing process and the exact composition of the atropine dilutions. However, corneal penetration might significantly vary depending on preservatives, such as benzalkonium chloride (BAC), and the atropine concentration. Since there is a trade-off between side effects, stability, and optimal effects of atropine on myopia, it is important to gain better knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 72 publications
0
12
0
1
Order By: Relevance
“…Stability of ophthalmic formulations is a valid aspect and it is important that the physicochemical characteristics of the formulation remain significantly unchanged for the appropriate period of storage or use from the start of manufacture [ 67 ]. The stability of ophthalmic formulations depends on a variety of factors, such as the stability of the active substance, temperature, storage conditions or excipients [ 90 ]. The formulations were stored at room temperature for 30 days after sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…Stability of ophthalmic formulations is a valid aspect and it is important that the physicochemical characteristics of the formulation remain significantly unchanged for the appropriate period of storage or use from the start of manufacture [ 67 ]. The stability of ophthalmic formulations depends on a variety of factors, such as the stability of the active substance, temperature, storage conditions or excipients [ 90 ]. The formulations were stored at room temperature for 30 days after sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings kann auch die Konzentration von 0,05 % mit einer Pupillenerweiterung von 3 mm einhergehen [ 35 ]. Konservierungsmittel haben keinen wesentlichen Einfluss auf die Penetration der Tropfen ins Auge [ 36 ]. Eine asiatische Studie hat keinen Unterschied bezüglich reduzierter Akkommodation und vergrößerten Pupillendurchmessers bei Konzentrationen zwischen 0,01 und 0,02 % gefunden [ 37 ].…”
Section: Interventionen Zur Progressionsminderungunclassified
“…Numerous studies have shown that low-dose (0.01%) atropine is effective in reducing the increase in myopia in adolescents, and topical atropine drops have been used for 150 years to relieve myopia [9–11] . However, long-term use can cause photosensitivity and rebound effects after drug withdrawal due to concentration-dependent side effects, so higher concentrations of atropine drops are still not widely used [12] …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, long-term use can cause photosensitivity and rebound effects after drug withdrawal due to concentrationdependent side effects, so higher concentrations of atropine drops are still not widely used. [12] At present, a large number of classic Chinese medicine decoctions have been used in clinical treatment of adolescent myopia, and they have been made into different dosage forms at the same time, with good effects. [13] However, there are many types of traditional Chinese medicine (TCM) decoctions in clinical application, and there is no interactive comparison between them.…”
Section: Introductionmentioning
confidence: 99%